(untitled) (Modern education and development, 2025)
The language of people preserves and transmits invaluable information about its history, culture and everyday life from generation to generation. In addition, through language, people convey to subsequent generations their accumulated experience over centuries. Over time, everything might be destroyed-cities, buildings and other objects of material culture, but information about them is constantly preserved in the language. In the implementation of this function of the language, such units as phraseological units, proverbs and sayings play a significant role. That is why the comparative study of phraseology and of unrelated languages ​​remains one of the most relevant areas of modern linguistics.